Parent Cognitions of Factors Influencing Snack Intake of Their School-aged Children at Away-from-home Events (P11-109-19). (13th June 2019) - Eck, Kaitlyn; Delaney, Colleen; Byrd-Bredbenner, Carol
Abstract: Objectives: To qualitatively investigate the cognitions and decisions of parents of school-aged children vis-à-vis children's snacking at way-from-home events. Methods: Parents (n = 37) of 6- to 11-year-old children from NJ, WV, and FL participated in 1 of 13 focus groups conducted by trained moderators. Data were content analyzed by trained researchers according to standard procedures. Results: Parents (97% mothers) identified fruits, vegetables, pretzels, granola bars, muffins, and fish crackers as examples of healthy snacks. Although children frequently snacked at away-from-home events, many parents felt that it was not always realistic or important for children to consume healthy snacks at these events, particularly if children consumed an otherwise nutritious diet. Controlling the quality of snacks eaten away-from-home, particularly at school events, was a challenge for parents. When faced with the responsibility of supplying healthy snacks for a group of kids at an away-from-home event, barriers parents encountered were children's preferences for unhealthy snacks, cost, and food allergies. Some parents identified school policies as a barrier to providing healthy snacks, noting that schools required parents to supply snacks that were packaged, store-bought, and did not require refrigeration. Parents also reported that providing healthy snacks was time consuming, citing the time required to peel and cut fruits and vegetables or prepare a healthy muffin recipe. Parents reported that some school policies, such as the "no party rule" and guidelines for healthy snacks at celebrations facilitated provision of healthy snacks by parents. Parents also indicated that serving fruits/vegetable in interesting ways (e.g., with dip, cut into shapes) increased the likelihood kids would accept these healthy snacks. Parents thought schools could help parents by providing a list of healthy, affordable, low allergen and easy-to-prepare and store snacks that are well accepted by kids. Conclusions: Parents identified numerous barriers to ensuring kids have healthy snacks at away-from-home events. Future nutrition interventions should help parents develop strategies to overcome these barriers and develop school policies supportive of healthy snacking. Funding Sources: 2011-68001-30170 and 2017-680001-26351.